Effects of natural-based SiO2 nanocoolant on car radiator : Thermal profile - Ruey Ong, Huei; Wan, Mohd Eqhwan Iskandar; Yapp Joo, Ming; Khan, Maksudur Rahman Md; Muhammad Khairul Anuar, Mohamed (Elsevier Ltd, 2022)
Nanofluid as a transport medium has a great deal of potential in heat transfer engineering applications. In this work, nanosilica was derived from natural sources, rice husk through incineration and chemical treatment process. Various SiO2 nanoparticle volume concentrations (0–1 vol%) were dispersed in EG/water binary mixture assisted by ultrasound technique to produce SiO2 nanocoolant. Scanning Electron Microscopy (SEM) was used to identify the surface morphology and size of the nanosilica. Furhermore, the study was further conducted in a car radiator to determine the thermal profile consists of the effect of nanoparticle concentration and the longevity testing of the nanocoolant. Findings show that nanosilica particles were in range of 15–25 nm with irregular shape. Moreover, the heat transfer performance was enhanced as the SiO2 concentration was increased. Apart from that, SiO2 1 vol% shows a great thermal behaviour as it takes a shorter time to achieve and maintain at optimal working temperature compared to other samples. Apart from that, it can be observed that SiO2 nanocoolant possesses slightly higher properties than the base fluid and conventional coolant. The results also revealed the average heat transfer coefficient is directly proportional to the volume concentration of nanofluids and the heat transfer performance of the radiator increased with the inclusion of nanoparticles to the base fluid.